Factors associated with avascular necrosis of the femoral head and nonunion in patients younger than 65 years with displaced femoral neck fractures treated with reduction and internal fixation (2013)
Introduction: Few studies have evaluated treatment of displaced femoral neck fractures in patients younger than 65 years, and risk factors for AVN or nonunion have not been clearly delineated within this age range. Method: To determine factors associated with avascular necrosis of the femoral head (AVN) and nonunion in patients younger than 65 years with displaced femoral neck fractures treated with reduction and internal fixation, we conducted a retrospective study of 29 displaced femoral neck fractures in 29 consecutive patients treated at a single institution. The influence of age, trauma energy, open reduction, and time from fracture to treatment on development of AVN and nonunion was evaluated. Results: Patients who developed AVN were significantly older and suffered lower energy trauma than cases without AVN. No recorded variables were associated with nonunion. Logistic regression determined that only age was independently associated with AVN. Age was a good predictor for developing AVN, with a C statistics of 0.861, and a best cutoff determined at 53.5 years. Conclusion: Patients between 53.5 and 65 years presented a higher risk of AVN. A primary arthroplasty should be considered in this subgroup. © 2012 Springer-Verlag.